2014
DOI: 10.1080/13803395.2014.955784
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel task for investigating decision making in a social context following traumatic brain injury

Abstract: The SDMT offers a novel way of examining decision making within a social context following TBI and may also be useful in other populations known to have specific social cognition impairment. Future research should aim to provide further clarification of the mechanisms of action and neuroanatomical correlates of poor performance on this task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 91 publications
1
9
0
3
Order By: Relevance
“…Individuals with the lesion in orbito-frontal cortex caused by TBI remained intact in the affective aspect (10). On the other hand, individuals with TBI were impaired in both aspects of ToM in this task (4,45,53,54). In 'the awareness of social inference test' (cognitive and affective ToM), persons with TBI were impaired (52,53,60,61).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with the lesion in orbito-frontal cortex caused by TBI remained intact in the affective aspect (10). On the other hand, individuals with TBI were impaired in both aspects of ToM in this task (4,45,53,54). In 'the awareness of social inference test' (cognitive and affective ToM), persons with TBI were impaired (52,53,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, individuals with TBI were impaired in both aspects of ToM in this task (4,45,53,54). In 'the awareness of social inference test' (cognitive and affective ToM), persons with TBI were impaired (52,53,60,61). In advanced task of 'reading the mind in the eyes' (affective aspect), individuals with TBI were impaired (25, 42-44, 46, 52, 54, 57, 61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como se mencionó anteriormente, un proceso de la cognición social son los juicios morales, que se deterioran en personas con daño cerebral como el tCe (Kelly, McDonald, y Kellett, 2014). La toma de decisiones morales hace referencia a la evaluación que hace el sujeto basado en la adecuación de la propia conducta y la de los demás | PsyChol.…”
Section: Introductionunclassified
“…When a hint is made, the underlying meaning of the request needs to be inferred by the listener on the basis of contextual cues. In a recent study, using short written texts adapted from the Hinting Task (Corcoran, Mercer, & Frith, 1995) we found that people with TBI had difficulty comprehending hints of varying levels of indirectness (Kelly, McDonald, & Kellet, 2014). This suggested that adults with TBI were less able than their non-injured counterparts, to interpret an ambiguous statement to infer what the speaker might mean based on common knowledge of conversational behaviour.…”
mentioning
confidence: 97%